A meta‐analysis of bariatric surgery‐related outcomes in accredited versus unaccredited hospitals in the United States. Issue 1 (11th November 2019) - Baidwan, Navneet K.; Bachiashvili, Vasil; Mehta, Tapan
Summary: The American Society for Bariatric Surgery established a set of standards for bariatric surgery Centers of Excellence accreditation programme in 2003. While several research efforts have shown that post‐bariatric surgery outcomes were poorer in unaccredited as compared to accredited hospitals, others have questioned the same. This research effort sought to use random effects meta‐analysis to quantitatively summarize the existing research efforts analysing this association, which were published between January 2000 and October 2018. Out of the total 559 articles, 13 that quantitatively analysed the effect of accreditation on post‐operative mortality‐ and morbidity‐related outcomes were included in the analysis. Overall, the weighted pooled estimates showed that compared to accredited, in the unaccredited hospitals, the odds of mortality were twice as high (odds ratio: 1.83; confidence interval: 1.49, 2.25), and those for morbidity were 1.23 times higher (1.11, 1.36). Estimates varied by the data source used, and the effect estimate used (odds or risk ratios). Overall, the odds of poor post‐operative outcomes were higher among unaccredited hospitals as compared to accredited. However, there were analytic differences and other limitations among the existing efforts. Future research efforts conducting independent analyses on these data sources, keeping the methodology consistent are needed.